The Role of Quranic Stories in Promoting Psychological Well-Being and Social Harmony - Ruslan Fariadi (Universitas PGRI Yogyakarta, 2026)
Mental health has become an increasingly primary global concern. The Qur’an, as a divine revelation, holds significant potential to influence human psychology. Numerous studies indicate that reading the Qur’an can positively contribute to mental well-being. Among its many aspects, Qur’anic stories play a central role in shaping psychological stability and fostering social harmony. This study employs a qualitative design using secondary data. Relevant articles and books were collected from Google Scholar and analyzed thematically through psychological and Qur’anic perspectives. The findings reveal that Qur’anic stories promote psychological well-being and social harmony by integrating the processes of learning, teaching, and preaching. These processes strengthen both intrapersonal and interpersonal phases of human development. This mechanism reflects the Prophet Muhammad’s (PBUH) emphasis on ‘allama al-Qur’an (learning the Qur’an, intrapersonal) and ta’allama al-Qur’an (teaching and preaching the Qur’an, interpersonal). Through these two phases, communities are encouraged to mitigate and reduce mental health challenges, ultimately supporting individual and collective well-being. Keywords: qur’anic stories, mental health, psychological well-being, social harmony, intrapersonal and interpersonal development